Which perspectives for work in agriculture? Food for thought for a research agenda - Dedieu, Benoît; Nettle, Ruth; Schiavi, Sandra Mara de Alencar; Sraïri, Mohamed Taher; Malanski, Priscila Duarte (Frontiers in Sustainable Food Systems, 2022)
The 2nd International Symposium on Work in Agriculture (March 29 – April 1 2021) was a moment of debates on the perspectives of work in agriculture that we try to summarize in this paper, through a bibliometric analysis and a transversal expert synthesis. Farming work and drivers of employment were the main topics of the presentations. OECD and Global South countries face different labour productivity dynamics. Some question are continent specific: will OECD lead to an agriculture without farmers? Will agriculture provide decent and attractive works to youth notably in the SSA continent? With what model of agriculture? But other issues are common: the ability of agroecological transition to improve working conditions and provide new jobs; the recognition of the women contribution to work and to decisions. The digital revolution and the migration flows from rural areas to cities and from are also deeply changing the agricultural work. Cross cutting perspectives are introduced, notably the potential of the territorial approach of work to develop interdisciplinary and transdisciplinary viewpoints and perspectives that are shared with all the stakeholders.